Broadband terahertz holography using isotropic VO2 metasurfaces - Jiayu Zhao; Runxuan Zhang; Sicheng Cao; Mingwei Zhuang; Zhengyong Song (Scientific Reports)
Abstract Vanadium dioxide (VO2) exhibits exceptional phase transition characteristics that enable dynamic manipulation of electromagnetic wave. In this study, a novel design of bilayer isotropic metasurface is introduced. It leverages insulating-to-metallic phase transition of VO2 to enable broadband holography for terahertz wave. For the metallic VO2, the upper VO2 antennas reflect incident terahertz wave and generate hologram. For the insulating VO2, incident wave is reflected by the lower gold antennas and the same hologram is generated with frequency doubling. Working frequencies of the designed holograms are 1.2 THz for metallic VO2 and 1.9 THz for insulating VO2. Due to the broadband performance under each state, the proposed metasurface can achieve holography within 1.0-2.1 THz. It is noteworthy that the generated holograms under two states of VO2 remain entirely independent, and another metasurface that achieves frequency-multiplexed holograms is presented. Our design may have possible applications in holographic display and information encryption.